2004
DOI: 10.1021/ic048661a
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Pathways for the Oxygenation of a Ruthenium(II) Dithiocarbamate Complex:  S-Oxygenation and S-Extrusion

Abstract: The reactions of Ru(bpy)(2)(N,N-dimethyldithiocarbamate)(+), 1, with O-atom-transfer reagents such as hydrogen peroxide, m-chloroperoxybenzoic acid, and oxone have been studied and several resulting derivatives isolated and structurally characterized. Both S-oxygenation and S-extrusion may occur depending upon reagent and conditions. Excess peroxygenation leads to a stable dioxygenate, Ru(bpy)(2)(N,N-dimethylthiocarbamatesulfinate-S,S)(+), 3. Stoichiometric oxygenation leads to mixtures of products from which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…In this regard, sulfur oxygenation and extrusion have been proposed as modes of the xenobiotic activation of DSF 11,12 and also as possible sources of its neurotoxicity . We have recently shown that similar sulfur oxygenation and extrusion may occur within a metal−DTC complex …”
Section: Discussionmentioning
confidence: 97%
“…In this regard, sulfur oxygenation and extrusion have been proposed as modes of the xenobiotic activation of DSF 11,12 and also as possible sources of its neurotoxicity . We have recently shown that similar sulfur oxygenation and extrusion may occur within a metal−DTC complex …”
Section: Discussionmentioning
confidence: 97%
“…Ruthenium−sulfur complexes with sulfur-donor ligands are well known for their industrial applications in hydrodesulfurization (HDS) and related processes, , partly because of the high catalytic activity of RuS 2 in various hydrogenation processes. , The chemistry of ruthenium complexes with dithioacid-based ligands such as dithiocarbamate and dithiocarbonate has been the subject of continuous study to date; however, the corresponding chemistry of dithiophosphate and dithiophosphonate has not been well developed. , Indeed, thiophosphorus species are an important class of sulfur-donor ligands . For example, the notable Lawesson’s dimer [( p -C 6 H 4 OMe)P(S)(μ-S)] 2 can undergo a ring-opening reaction by nucleophilic attack under suitable conditions, resulting in formation of the typical dithiophosphate and dithiophosphonate ligands. Even though the synthesis and characterization of thiophosphorus ligands [(RO) 2 PS 2 ] − and [(RO)RPS 2 ] − of a few transition metal derivatives have been investigated in depth, very little is known about the chemistry of ruthenium-dithiophosphonate and -dithiophosphonate complexes. , Similarly, although the coordinative behavior of ferrocenyl-dithiophosphonate [FcP(OR)S 2 ] − (R = Me, Et, i -Pr, and CH 2 C 6 H 4 N 3 , Fc = Fe(η 5 -C 5 H 4 )(η 5 -C 5 H 5 )) with transition metals was recently studied by Woollins and Süss-Fink et al, no ruthenium complex with ferrocenyl-phosphonodithiolate as a dithio ligand has been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…Often times, [Ru II (bpy) 2 L] 2+ complexes are utilized to initiate such photochemical redox reactions due to well-characterized electron transfer reactivity from long-lived luminescent states. 27 The general family of low spin d 6 [Ru II (bpy) 2 L] 2+ complexes is also quite inert, which allows characterization of unusual ligand-based reactivity; we have used such complexes to characterize products of O atom exchange and S atom extrusion reactions of Ru-bound dithiocarbamates, 28 as well as oxidative and photoinduced C− H activation of Ru-bound heterocycles. 29,30 We recently reported that photooxygenation of a Ru(II) flavonolate complex, using excitation at longer wavelengths than 400 nm, generates a unique Ru-bound 2-benzoatophenylglyoxylate (Ru-bpg) complex resulting from a 1,2 addition pathway, shown in Scheme 2, whereas broad-band excitation yields product mixtures derived from 1,3-addition and loss of CO. 31 In this report, we investigate the possible mechanistic pathways of this reactivity using a series of analogous Ru(II) bis-bipyridyl flavonolate complexes, [Ru II…”
Section: ■ Introductionmentioning
confidence: 99%